Influência da qualidade do habitat para a produção pesqueira: o papel dos manguezais sobre a ictiofauna de um estuário do Ceará - Brasil - Vasconcelos Filho, José Ivan Fonteles de (2021)
Mangroves are believed to be indispensable for the productivity of coastal fisheries, acting as nursery areas and playing a significant role in the ecology of several tropical fish species of economic and ecological importance. However, these forests continue to face different processes of degradation and although the use of mangroves by ichthyofauna is well documented, this approach is rarely used to analyze the relationship between the conservation status of the habitat and its influence on fisheries. In this context, the objective of this work is to evaluate the influence of the state of conservation of mangroves on fish populations with ecological and economic interest in the municipality of Acaraú - CE, as well as to characterize the species associated with these environments. For this, bimonthly sampling was carried out between the months of July/2019 to May/2020. The collections were made using tarrafas, always during the low tide. All captured fish were placed in plastic bags previously identified with the data from each sampled area and stored in Styrofoam boxes with ice for transportation to the laboratory, where they were identified, measured, and dissected. In all, 1,713 individuals were collected, distributed among 37 species, 27 families. The families Gerreidae and Lutjanidae were the most representative in the estuary, comprising together 58.14% of the samples. Approximately 86.48% of the species collected, except for Batrachoididae, Gobiidae, Uranoscopidae and Tetraodontidae are of fishing interest. The species with no commercial value are captured as accompanying fauna and then discarded in the environment by the fishermen, and even those that are commercially important are eliminated because they are not large enough to be sold. Of these, endangered species such as Megalops atlanticus, Hippocampus erectus, Lutjanus analis, Lutjanus jocu, and Mycteroperca bonaci were also recorded. The results obtained showed that the ichthyofauna showed spatial variations in its composition, especially in the abundance of individuals, so that the most conserved mangrove forests had the highest representation of species and individuals. However, there were no seasonal differences in the composition of the ichthyofauna and environmental variables. Thus, salinity and Landscape Development Intensity Index (IDP) were the main environmental variables responsible for the spatial distribution and composition of the ichthyofauna. The species Eucinostomus argenteus, Diapterus auratus, L. jocu and L. alexandrei were dominant in the estuary throughout the sampling period, together amounting to 52.06% of total sampling. As for the ecological categories, the ichthyofauna collected was predominantly marine dependent, corresponding to 81.49% of the individuals, probably due to the high levels of salinity of the water, which varied between 35 and 47 ppm throughout the year. Considering the trophic categories, the highest representation was of the piscivorous/zoobentivorous species, with a strong proportion of predatory species and comprising 48.56% of the samples. There were no significant seasonal and spatial differences between species dominance and the ecological and trophic categories. Although mangroves are preferred sites in the reproductive context, few fish species were found in reproductive stage. About 92% of the sampled ichthyofauna was composed of young individuals that use the estuary as feeding and nursery areas. The highest abundance of individuals was found in the most conserved mangrove forests, which allows us to infer that the destruction of these ecosystems could considerably compromise the number of fish produced. The four mangrove forests studied presented conditions favorable to the growth and health status of the species evaluated. However, the mangrove forest in Arpoeiras, with the lowest IDP values offered better conditions than the more degraded mangrove forests, so that the high productivity and low predation pressure conferred by the more conserved mangroves were of great relevance for the maintenance of favorable conditions for the population stocks. Still, other studies on the ichthyofauna in estuarine mangroves are needed so that management projects and more efficient monitoring plans can be developed.